Metal Complexation Studies of 1-(4-Carboxy-3-hydroxy-N-methyl phenyl- amino methyl) 2-methyl perimidine - Umang N. Patel; Arun Singh (E-Journal of Chemistry)
Aminomethylation of 2-methyl perimidine was carried out by treating 2-methyl perimidine with formaldehyde and 4-aminosalicylic acid. The resultant compound was designed as 1-(4-caroxy-3-hydroxy-N-methyl phenylamino methyl)2-methyl perimidine. The transition metal complexes of Cu2+, Co2+, Ni2+, Mn2+ and Zn2+ have been prepared and characterized by elemental analysis, spectral studies, magnetic moment determination, molar conductivity measurement and antimicrobial activity.